Analisis Kesulitan Membaca (Disleksia) pada Anak Tunagrahita di SLB Negeri Autis Sumatera Utara - Salimatul Islamiyah; Sri Puspita Della Aryadi; Viny Syahputri; Yusra Faizah; Muhammad Nur Huda; Rizky Ramadhan Damanik; Ali Pernantian Pane (Jurnal Bintang Pendidikan Indonesia, 2025)
The journal aims to explore the various challenges faced by students in the learning process, particularly focusing on the factors contributing to learning difficulties. Employing qualitative research methods, the study gathers data through interviews, observations, and literature reviews to understand the experiences of students with learning difficulties. Key findings indicate that these difficulties can stem from a combination of cognitive, emotional, and environmental factors, highlighting the importance of early identification and intervention to support affected students. The journal emphasizes the need for educators and policymakers to develop tailored strategies and resources to assist students facing learning challenges. Additionally, it recommends future research to explore specific interventions and their effectiveness in diverse educational settings. Ultimately, addressing learning difficulties is crucial for fostering an inclusive educational environment that promotes the success of all students.